The rhetorical purpose of Israel's notion of the 'whole body' as the ideal body in the psalms: A comparative study of selected psalms from four different genres - Wessels, Cornelius J. J.; Coetzee, Johan H. (Verbum et Ecclesia, 2013)
The authors of the psalms implemented body rhetoric, especially the notion of the ‘whole body’ as the ideal body, in the various genres of psalms, with specific purposes in mind. The whole body as ideal body served as a defining paradigm within the ancient Israelite culture. In this article, the relationship between the embodied God-concept, the ideal societal body and the individual body is investigated in order to determine the purpose of the implementation of this ideology of whole-bodiedness in selected psalm genres. In Psalm 2, the political body as cultural construct plays a prominent role in directing the individual to think of the body in a specific manner. In Psalm 6, the ‘broken body’ drives the lamentation of the psalmist towards recovery. Psalm 29 reflects the poet’s ability to sketch, in hymnic-embodied language, God’s relationship with his creation and his people and the poet’s worship for God’s fullness of existence and activity. Psalm 32, as a psalm of thanksgiving, pictures God as the whole body in terms of the saviour, protector and healer of the broken (sinful) body.
free